Titia vem cá ver a pedra alumiante que o papai trouxe'. História da Ciência, Radioatividade e o Césio-137 em Goiânia: propostas para uma unidade didática - Gomes, Paulo César [UNESP]; Lopes Júnior, Jair [UNESP]; Delarole, Regiane [UNESP] (My University, 2015)
This study aimed to discuss the recent contributions of History of Science to theteaching of chemistry. The theme of the teaching unit was on the accident of cesium-137 in Goiânia ? Goiás, Brazil (1987). This was a qualitative study in which researcherand professor use the methodology of teaching on research. Thus, students should seekinformation, organize the data collected and establish relationships. Students producedposters in an exhibition at the school on the twentieth anniversary of the accident.Results demonstrated the importance of this resource. It was possible to exploit theabundance of detail and illustrations utilized what themes they students considerimportant and which they exploited. A poster exhibition on the theme indicated thestrong interest of students to participate in all activities proposed. The study alsorevealed the importance of using elements of the History of Science in ChemicalEducation and its relationship to the daily life of students.Key words: history of science; radioactivity; cesium-137

O estudo objetivou discutir contribuições da história da ciência recente ao ensino dequímica tendo como temática a estruturação de uma unidade didática sobre o acidentedo césio-137 em Goiânia - Goiás, Brasil (1987-2007). Tratou-se de uma PesquisaQualitativa na qual pesquisador e professor adotaram a utilização da metodologia doEnsino por Investigação na qual os alunos deveriam buscar informações, organizardados coletados, formular hipóteses e estabelecer relações. Dentro da linguagem dosquadrinhos, os alunos produziram cartazes para uma exposição na escola sobre ovigésimo aniversário do acidente. Os resultados demonstraram que este recursopossibilitou explorar a riqueza de detalhes nas ilustrações utilizadas. A linguagem dosquadrinhos é integrante do cotidiano dos alunos e eles têm facilidade em expor suasideias através dela. A exposição dos cartazes sobre a temática denotou o grandeinteresse dos alunos em realizar e participar de todas as atividades propostas.
History of science, radioactivity and cesium-137 in “goiânia”: a proposal for teaching unit
Keywords: History of science; Radioactivity; Cesium-137; Hiistória da ciência; Radioatividade; Césio-137